User-centred design approach for hydrotherapy wetsuit. Issue 1 (2nd January 2016) - Han, Fred; Shin, Kristina; Chow, Daniel
ABSTRACT: This paper describes a user-centred design approach to hydrotherapy wetsuit prototype development for people with limited mobility. Current hydrotherapy devices are not versatile enough to meet the varied rehabilitation needs and it usually requires the involvement of at least two helpers. This makes the hydrotherapy less cost-effective amongst other physical therapies and thus less desirable to public healthcare providers. Therefore, the project aims to design a hydrotherapy wetsuit that would reduce the hydrotherapy cost while improving the patient's quality of life. With close user involvement throughout the development process, a user-operated adaptive hydrotherapy wetsuit is designed and tested.